Muscular TOR knockdown and endurance exercise ameliorate high salt and age-related skeletal muscle degradation by activating the MTOR-mediated pathway - Shi-Jie Wang; Deng-tai Wen; Ying-hui Gao; Jing-feng Wang; Xing-feng Ma (PLoS ONE, 2025)
The target of rapamycin(TOR)gene is closely related to metabolism and cellular aging, but it is unclear whether the TOR pathways mediate endurance exercise against the accelerated aging of skeletal muscle induced by high salt intake. In this study, muscular TOR gene overexpression and RNAi were constructed by constructing MhcGAL4/TOR-overexpression and MhcGAL4/TORUAS-RNAi systems in Drosophila. The results showed that muscle TOR knockdown and endurance exercise significantly increased the climbing speed, climbing endurance, the expression of autophagy related gene 2(ATG2), silent information regulator 2(SIR2), and pparγ coactivator 1(PGC-1α) genes, and superoxide dismutases(SOD) activity, but it decreased the expression of the TOR gene and reactive oxygen species(ROS) level, and it protected the myofibrillar fibers and mitochondria of skeletal muscle in Drosophila on a high-salt diet. TOR overexpression yielded similar results to the high salt diet(HSD) alone, with the opposite effect of TOR knockout found in regard to endurance exercise and HSD-induced age-related skeletal muscle degradation. Therefore, the current findings confirm that the muscle TOR gene plays an important role in endurance exercise against HSD-induced age-related skeletal muscle degeneration, as it determines the activity of the mammalian target of rapamycin(MTOR)/SIR2/PGC-1α and MTOR/ATG2/PGC-1α pathways in skeletal muscle.